PENGARUH LINGKUNGAN KERJA FISIK DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT INDOFOOD MAKMUR TBK DI PEKANBARU - Yohanes, Joni; Rifqi, Ahmad; ', Nuryanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at PT. Indofood Makmur Tbk Pekanbaru branch with the purpose to determine the effect on variable Work Environment Physical and Cultural Organization simultaneously the Employee Performance PT. Indofood Makmur Tbk Pekanbaru branch. This study uses primary data obtained from interviews and giving questionnaires to all employees of PT. Indofood Makmur Tbk Pekanbaru branch. Secondary data were obtained relating to the object and the organizational structure of the population in this study were all employees who were 75 people and sampled. The analytical method used in this study is the linear regression method multiple. From results of testing that was done, simultaneous regression test (Test-F) indicates that the variable Work Environment Physical and Cultural Organization simultaneously significant effect on employee performance. From the results of the partial test (t-test) showed that the variables of Physical Work Environment and Cultural Organization significant effect on employee performance. The result of the calculation of the coefficient of determination (R2) is approximately 0.583, or by 58.3%, which means, the variable Work Environment Physical and Cultural Organization jointly influence on employee performance, while the remaining 41.7% is influenced by other variables not examined in this research.Keywords : Physical Work Environment, Organizational Culture and Employee Performance